Determination of non-steroidal estrogens in breast milk, plasma, urine and hair by gas chromatography/mass spectrometry - Choi, MH; Kim, KR; Hong, JK; Park, SJ; Chung, BC (WILEY, 2002)
It is suspected that all the natural estrogens occurring in the human body, as well as dietary and synthetic estrogens, diversely affect the endocrine system depending on their exposure patterns. More rapid, reliable and accurate measurements of these compounds in various biological matrices are thus becoming an important task. After solid-phase extraction using an Oasis HLB extraction cartridge, the estrogen concentrates were derivatized with a mixture of N-methyl-N-trifluoro-trimethylsilylacetamide/ammonium iodide/dithioerythritol (1000:4:5, v/w/w) for analysis by gas chromatography/mass spectrometry in the selected ion-monitoring (SIM) mode. The qualitative identification of estrogens detected in SIM mode was further confirmed by tandem mass spectrometry using low-energy collision-induced dissociation (CID) mode. The method for the assay of the 20 estrogens was linear over the ranges of 1-1000 mug/L for biological fluids and 1-200 mug/kg for hair with high correlation coefficient (>0.99). The limits of quantitation (LOQ) ranged from 1.0-10 mug/L (or mug/kg) and the limit of detection ranged from 0.2-3 mug/L (or mug/kg). The average precision (% CV) and accuracy (% bias) of the method determined at the LOQ low, and medium concentrations were in the ranges 2.6-9.2 and -4.1-7.7, respectively. The average extraction recovery of the estrogens from plasma and hair at the three concentration levels varied in the ranges 77-103% (1.9-14.3% CV) and 73-104% (3.1-14%), respectively. The distribution patterns of the estrogens were characteristic of each biosample. Five estrogens in the range 1.5-44.9 mug/L were measured in breast milk, 8 estrogens in the range 3.5-322 mug/L in plasma, 12 estrogens at 1.2-442 mug/L in urine, and biochanin-A at 13.2-39.1 mug/kg in hair. Because of its high sensitivity, good precision and specificity, the present method was found suitable for the trace analysis of dietary and synthetic estrogens in complex biosamples such as breast milk, plasma, urine and hair. Copyright (C) 2002 John Wiley Sons, Ltd.
Keywords: PHYTO-ESTROGENS; 5-ALPHA-REDUCTASE; TRIMETHYLSILYL; PHYTOESTROGENS; STEROIDS; CANCER; DES; MS